-5a+12+7a=2a-4a

Simple and best practice solution for -5a+12+7a=2a-4a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5a+12+7a=2a-4a equation:


Simplifying
-5a + 12 + 7a = 2a + -4a

Reorder the terms:
12 + -5a + 7a = 2a + -4a

Combine like terms: -5a + 7a = 2a
12 + 2a = 2a + -4a

Combine like terms: 2a + -4a = -2a
12 + 2a = -2a

Solving
12 + 2a = -2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '2a' to each side of the equation.
12 + 2a + 2a = -2a + 2a

Combine like terms: 2a + 2a = 4a
12 + 4a = -2a + 2a

Combine like terms: -2a + 2a = 0
12 + 4a = 0

Add '-12' to each side of the equation.
12 + -12 + 4a = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 4a = 0 + -12
4a = 0 + -12

Combine like terms: 0 + -12 = -12
4a = -12

Divide each side by '4'.
a = -3

Simplifying
a = -3

See similar equations:

| x^3-4x^2-14x-14=0 | | 9x+7=-38 | | 3a+7=b | | 3xa+7=b | | 20x^2+52x-24=0 | | 6t-t-3=4t-8 | | 176-y=253 | | (2e^2-5e)+(7e-3e^2)= | | 25x^4+259x^2+400=0 | | 3x+76.5= | | x+12y+16=0 | | .6x+.1y=.5 | | f(a+4)=6x+7 | | 4-6x=5-9 | | (t+4)(t+4)=54 | | -27x=81 | | 142.5*20=91 | | 142.5*91=20 | | x=400+-1y | | 6x+18=12-9 | | 142.5*91=20*x | | 8x+21=6x+69 | | 2x-4=7x-7-5x | | 142.5=20*91 | | 4x+35=14x+45 | | 0.7x=0.9+0.2x | | -4+2x=-8+24 | | 7y+10=2y+25 | | 4x+21=5x | | 1x+1y=400 | | 8.2x+24.88=-11.8x+24.10 | | 5x+3x=20x |

Equations solver categories